Risk Factors of Autism Spectrum Disorders in Children - Irum Aslam, Muhammad Yousuf, Iram Nawaz, Naveed Anjum, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To find out demographical, medical, familial and parental risk factors of ASD in children. Study Design: Case-control study. Place and Duration of the Study: The department of Pediatric Neurology, The Children’s Hospital & Institute of Child Health, Multan, Pakistan from November 2019 to April 2020. Methodology: A total of 120 children (60 cases and 60 controls) of both genders aged up to 12 years were enrolled. Diagnosis of ASD was made as per DSM-IV-TR criteria. Demographical and medical characteristics along with familial and parental data were noted. Chi-square test was employed considering p<0.05 as significant to compare study variables between cases and controls. Results: In a total of 120 children, 72 (60.0%) children were male. Overall, mean age was noted to be 4.82±3.5 years while 77 (64.2%) children were ≤ 5 years of age. In comparison to controls, lack of breastfeeding up till 2 years of age (p=0.0009), asthma (p=0.0367), hearing impairment (p=0.0408) and allergy to milk or wheat (p=0.0475) were found to be significant risk factors among children with ASD while remaining all other characteristics were not found to have any significant relationship (p>0.05) with ASD. It was observed that maternal education status as illiterate (p=0.0267) and immediate family history of ASD (p=0.0475) were significantly associated risk factors for ASD among cases wile all remaining factors were not found to have any significant association (p>0.05). Conclusion: Lack of breastfeeding up till 2 years of age, presence of asthma, hearing impairment and allergy to milk or wheat were found to be significant risk factors among children with ASD. Maternal education status as illiterate and immediate family history of ASD were also noted to be significantly associated risk factors for ASD.